Blended Finance For Impact: Financing The Nambo Waste Treatment Facility Through Innovative Infrastructure Finance Scheme - Asa, Surya Pagi (Green Publisher Indonesia, 2025)
The Intermediate Treatment Facility (ITF) Nambo is a waste processing infrastructure project in West Java that has faced long delays due to financial and institutional challenges. Although the project was initially tendered using a public-private partnership (PPP) scheme, it failed to achieve financial close due to equity constraints, absence of certainty in revenue from output, and limited access to long-tenor loans. This study explores how blended finance can be used to improve the financial viability and bankability of the project. Using data from the 2015 Final Business Case and 2022 Feasibility Study, six financial scenarios were modeled to assess the impact of key variables including debt-equity ratio, RDF pricing, loan rate and tenor, and concessional finance instruments. The Development Finance Institution (DFI) Enhanced Principle is also used to assess the feasibility of the project in incorporating blended finance. Results show that under baseline assumptions the project is marginally viable, but becomes unfeasible under more conservative market conditions. Incorporating concessional debt and a credit guarantee into the capital structure significantly improves financial viability. The optimal scenario shows a lowered WACC of 6.14%, an IRR of 6.47%, and a positive NPV, even with conservative RDF price assumptions. The project also meets the minimum debt service coverage ratio (DSCR) required by lenders. This study recommends a blended finance strategy that leverages concessional funding and credit enhancement to reduce risk, lower financing costs, and transform the project to become bankable thus catalyze private investment. It provides practical insights for policymakers and developers to unlock financing for high-impact infrastructure projects in emerging sectors like waste management.